INNOVATIVE SYSTEMS PORTFOLIO - Sethi, Ashwani; Arora, Sunny (International Journal of Psychosocial Rehabilitation, 2021)
The efficiency of our workplaces may be substantially improved by the use of artificial intelligence. The human workforce is freed up to focus on tasks that require creativity and empathy, among other skills, when AI is used to perform repetitive or dangerous tasks. The technology's complexity and manufacturers' lack of confidence in its capabilities are major impediments to widespread AI deployment. If we don't have any experience in data science, it's difficult for us to grasp how predictive modelling or data science works